2015
DOI: 10.2174/1567205012666150204125732
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Platelet APP Isoform Ratios in Autosomal Dominant Alzheimer’s Disease: Baseline Data from a DIAN Cohort Subset

Abstract: Introduction This study examines platelet amyloid precursor protein (APP) isoform ratios of 120KDa to 110KDa (APPr) between mutation carriers (MC) carrying a mutation for autosomal dominant Alzheimer’s disease (ADAD) and non-carriers (NC). Two previous studies reported no significant difference in APPr between ADAD MC and NC, which may have been due to the small sample size in both studies. The current study examines APPr in MC versus NC in a larger sample. In addition, it investigated whether APPr correlate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This particular type of metabolic pattern is also found in natural killer cells 41 . PFKP, which enhanced in clear cell renal cell carcinoma 42 , non-small cell lung cancer 43 , and acute myelogenous leukemia 44 , contributes to glycolysis, to maintain the malignancy of the disease. In this study, we found that PFKP is transcriptionally regulated by oxidized ATM-mediated HIF1A under hypoxia, which is similar to the findings in human skin fibroblasts stimulated by T 3 45 and in human endothelial cell lines in response to hypoxic stress 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This particular type of metabolic pattern is also found in natural killer cells 41 . PFKP, which enhanced in clear cell renal cell carcinoma 42 , non-small cell lung cancer 43 , and acute myelogenous leukemia 44 , contributes to glycolysis, to maintain the malignancy of the disease. In this study, we found that PFKP is transcriptionally regulated by oxidized ATM-mediated HIF1A under hypoxia, which is similar to the findings in human skin fibroblasts stimulated by T 3 45 and in human endothelial cell lines in response to hypoxic stress 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the discrepancy in bone mineral content found due to WBV may be explained by the fact that a prolonged time period of WVB training might deregulate the values of intracellular and circulating SMP30. In addition, protein platelet content has previously been used as marker cells during the appearance and progression of several pathologies of different nature, such as Alzheimer's and cancer [49,50]. So it could be possible that WBV would increase the plasma concentration of SMP30, by inducing their hyperproduction from the liver and kidney, but also by mobilizing cell deposits, as evidenced by the SMP30 mobilization from platelets in the WBV program demonstrated here.…”
Section: Discussionmentioning
confidence: 71%
“…Such assays contribute to the ongoing efforts in developing diagnostic tools and markers that can aid in the early detection and differentiation of neurodegenerative disorders. Evidence suggests that altered APP processing occurs before clinical manifestations in AD patients with mutations associated with the autosomal dominant form of the disease [72]. This observation highlights the potential of APP isoforms in PLTs as surrogate biomarkers for assessing disease progression and treatment effectiveness.…”
Section: Unlocking the Role Of Platelets In Alzheimer's Diseasementioning
confidence: 82%